713. The Clinical Impact of Implementation of a Multidisciplinary Endocarditis Team. (31st December 2020) - El-Dalati, Sami; Cronin, Daniel; IV, James Riddell; Shea, Michael; Weinberg, Richard; Washer, Laraine; Stoneman, Emily; Perry, D Alexander; Bradley, Suzanne F; Bradley, Suzanne F; Burke, James; Murali, Sadhana; et al.
Abstract: Background: Infectious endocarditis is associated with substantial in-patient mortality of 15-20%. Effective management requires coordination between multiple medical and surgical subspecialties which can often lead to disjointed care. Previous European studies have identified multidisciplinary endocarditis teams as a tool for reducing endocarditis mortality. Methods: The University of Michigan Multidisciplinary Endocarditis Team was formed on May 3 rd, 2018. The group developed an evidence-based algorithm for management of endocarditis that was used to provide recommendations for hospitalized patients over a 1-year period. Mortality outcomes were then retroactively assessed and compared to a historical control that was identified using an internal research tool. Figure 1 Table 1 Results: Between June 14 th, 2018 and June 13 th, 2019 the team provided guideline-based recommendations on 56 patients with Duke Criteria definite endocarditis and at least 1 American Heart Association indication for surgery. The historical control included 68 patients with definite endocarditis and surgical indications admitted between July 1 st, 2014 to June 30 th, 2015. In-hospital mortality decreased significantly from 29.4% in 2014-2015 to 7.1% in 2018-2019 (p< 0.0001). There was a non-significant increase in the rate of surgical intervention after implementation of the team (41.2% vs 55.4%; p=0.12). Table 2 Table 3 Table 4 Conclusion: Implementation of a multidisciplinary endocarditis team was associated with a significant 1-year decrease in all-cause in-hospital mortality for patients with definite endocarditis and surgical indications. In conjunction with previous studies demonstrating their effectiveness, this data supports that widespread adoption of endocarditis teams in North America has the potential to improve outcomes for this patient population. Table 5 Disclosures: All Authors : No reported disclosures